Penggunaan Model Method untuk Meningkatkan Kemampuan Pemecahan Masalah Matematik Siswa Sekolah Dasar - Isnaini Handayani (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2015)
The purpose of this study is to examine the effect of the learning of model method for mathematical problem solving ability of elementary students. The design of the study is a pretest and posttest control of design group. The experimental group used learning of model methods and the control group used learning of conventional method. To obtain the data of the research result, the instrument used is in the form of mathematical problem solving ability test and the observation sheet. The population is the entire of the fifth grade of elementary school students throughout North Jakarta, with the sample of Tugu Utara Pagi 07 Elementary School for two classes which were chosen randomly. Data analysis is done quantitatively namely to the pretest data and normalized gain of mathematical problem-solving ability. This study is using the test of the difference of two populations. The result shows that the improvement of mathematical problem solving ability of the students who obtain the model method learning is better than the students who received the conventional method learning.